Self Esteem Enhancement among Youth with Disabilities - Aina Razlin, Mohammad Roose; Rafidah Aga, Mohd Jaladin; Janet Ann, Fernandez (University of Malaya Press, 2021)
Self-esteem has become one of the important elements for good life maintenance. Past studies revealed that self-esteem infuences people in various life aspects such as physical and mental health, financial, as well as personal fulfilment. This chapter discusses self-esteem among persons with disabilities in Malaysia and the discussion is divided into three parts. The first part of this chapter includes general information about self-esteem such as its definitions and conceptualizations, as well as models of self-esteem formation. The second part explains the general concepts of self-esteem, focusing on how low self-esteem can affect the quality of life of persons with disabilities. Later in this chapter, the causes, characteristics, impacts, and treatments of low self-esteem are elaborated. The last part of this chapter presents a low self-esteem intervention module for Malaysians with disabilities.